2010
DOI: 10.1111/j.1745-3933.2010.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Power and spectral index anisotropy of the entire inertial range of turbulence in the fast solar wind

Abstract: 12.12.13 KB. Ok to add the published version to spiral. RAS/ OUP policy

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
196
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(230 citation statements)
references
References 38 publications
32
196
2
Order By: Relevance
“…In the inertial range one observes a bifurcation of the two spectra: the perpendicular spectrum follows the Kolmogorov's slope, E(k ⊥ ) ∼ k −5/3 ⊥ , while the parallel spectrum is steeper, E(k ) ∼ k −2 . This result, initially seen in fast wind measured by Ulysses (Horbury et al 2008) has been confirmed by several other studies (Podesta 2009;Luo and Wu 2010;Wicks et al 2010Chen et al 2011a). These magnetic field spectral scaling observations provide an intriguing, if not unequivocal, connection to the Goldreich-Sridhar theory (Higdon 1984;Goldreich and Sridhar 1995).…”
Section: Magnetic Fluctuationssupporting
confidence: 77%
See 4 more Smart Citations
“…In the inertial range one observes a bifurcation of the two spectra: the perpendicular spectrum follows the Kolmogorov's slope, E(k ⊥ ) ∼ k −5/3 ⊥ , while the parallel spectrum is steeper, E(k ) ∼ k −2 . This result, initially seen in fast wind measured by Ulysses (Horbury et al 2008) has been confirmed by several other studies (Podesta 2009;Luo and Wu 2010;Wicks et al 2010Chen et al 2011a). These magnetic field spectral scaling observations provide an intriguing, if not unequivocal, connection to the Goldreich-Sridhar theory (Higdon 1984;Goldreich and Sridhar 1995).…”
Section: Magnetic Fluctuationssupporting
confidence: 77%
“…Courtesy of R. Wicks. The same figure as a function of kρ i can be found in Wicks et al (2010) AU from the Sun). As the spacecraft only measures wave vectors k parallel to V sw , for small flow-to-field angles θ BV ∈ [0, 10] • , P (nT 2 /Hz) represents an E(k ) spectrum, and for quasi-perpendicular angles θ BV ∈ [80, 90] • , P ⊥ (nT 2 /Hz), is the proxy of E(k ⊥ ).…”
Section: Magnetic Fluctuationssupporting
confidence: 58%
See 3 more Smart Citations